Answer:
x=3, y=9
Step-by-step explanation:
5x-2y=-3
4x-2y=-6
Then:
solve for y:
-2y=-6-4x
y=3+2x
Substitute y into either equation:
4x-2(3+2x)=-6
4x-6-4x=-6
-6=-6, use other equation
5x-2(3+2x)=-3
5x-6-4x=-3
x-6=-3
x=3
then:
y=3+2(3)
y=9
Answer:
Part A: Option 2, A: Anna’s answer is incorrect. She correctly factored out 5x, but incorrectly identified a and b, so her answer cannot be correct.
Part B: Option 3, B: 5x(x+2)(x^2−2x+4)
Step-by-step explanation:
p(x) = 5x^4 + 40x
p(x) = 5x(x^3 + 8)
p(x) = 5x(x + 2)(x^2 - 2x + 4)
Part A: Option 2, A: Anna’s answer is incorrect. She correctly factored out 5x, but incorrectly identified a and b, so her answer cannot be correct.
Part B: Option 3, B: 5x(x+2)(x^2−2x+4)
It's about 20 units
Hope this helped :)
Answer:
< No
Step-by-step explanation: